2012
DOI: 10.1002/mus.23430
|View full text |Cite
|
Sign up to set email alerts
|

Aging influences central motor conduction less than peripheral motor conduction: A transcranial magnetic stimulation study

Abstract: CCCT is the most direct indicator of corticospinal tract conduction, whereas L1-level latency reflects whole peripheral motor conduction. Central motor conduction was found to be relatively less affected by aging compared with peripheral motor conduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 26 publications
3
14
0
Order By: Relevance
“…This makes it possible to estimate the latency from cortex to conus (corticoconus conduction time) and the peripheral component of CMCT‐M (cauda equina conduction time). However, MATS‐based root latencies are relatively low, and corresponding CMCT‐M readings are relatively high when compared with results obtained using conventional coils (see Table S1 in Supplementary Material, available online) . Furthermore, root latencies are 0.9 ms shorter than for electrical root stimulation, equivalent to a distance of about 4.5 cm if a nerve conduction velocity of 50 m/s is assumed .…”
Section: Discussionmentioning
confidence: 94%
“…This makes it possible to estimate the latency from cortex to conus (corticoconus conduction time) and the peripheral component of CMCT‐M (cauda equina conduction time). However, MATS‐based root latencies are relatively low, and corresponding CMCT‐M readings are relatively high when compared with results obtained using conventional coils (see Table S1 in Supplementary Material, available online) . Furthermore, root latencies are 0.9 ms shorter than for electrical root stimulation, equivalent to a distance of about 4.5 cm if a nerve conduction velocity of 50 m/s is assumed .…”
Section: Discussionmentioning
confidence: 94%
“…Two main methods are used to calculate CMCT; one uses magnetic root stimulation [4][5][6][7] whereas the other uses F-waves. [2][3][4]8,9 The CMCT calculated by subtracting the F-wave latencies from the latencies measured to ADM after transcranial stimulation are slightly shorter than that obtained after magnetic root stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Matsumoto et al reported that corticoconus motor conduction time (CCCT) was less affected by aging than by PMCT. 6 The reason for this can be explained by anatomy; the brain and spinal cord are protected by the cranial bones and the vertebral column, respectively, but peripheral nerves are directly and easily affected by minor trauma. 6 CCCT was the conduction time from the motor cortex to the cauda equina at the L1 spinous process.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CMCT also shows a weaker correlation with aging than PMCT. 27 In some previous reports, the prolongation of CMCT and MEPs latency showed only small differences between the upper and lower limbs. [3][4] On the contrary, Lyu et al 12 reported that CMCT and MEPs latency in the upper limbs were longer than those in the lower limbs.…”
Section: C3-c4 (N = 25) Adm-cmct Ah-cmct Adm-meps Ah-mepsmentioning
confidence: 97%